Eksistensi Ilmu Medis dalam Literatur Bahasa Era Salafussaleh - Zaidaan, Farhan; Nahdliin, Maratun; Syifa, Najla Muthiah (Maliki Interdisciplinary Journal, 2025)
This article discusses the existence of medical science in linguistic literature during the Salafus Saleh era, covering the period of Prophet Muhammad (peace be upon him), his Companions, the Tabi’in, and the peak development during the Umayyad and Abbasid dynasties. Islam, as a comprehensive religion, emphasizes health, hygiene, nutrition, and medical ethics grounded in the values of justice, honesty, and public welfare. The approach used in this article is a conceptual analysis of classical and modern literature to describe the evolution and contributions of early Islamic medical scholars. The study shows that medical practice during the Prophet’s era was based on both spiritual and empirical values. During the Umayyad dynasty, the establishment of Bimaristan marked the institutionalization of Islamic medicine, while in the Abbasid era, medicine reached its golden age through the translation of medical texts and the monumental works of scholars such as Ar-Razi, Ibn Sina, and Al-Zahrawi. In conclusion, the development of medical science in Islamic civilization reflects an integration of revelation, reason, and empirical observation, contributing significantly to the advancement of global medical knowledge